Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae) - Uramoto, Keiko; Norrbom, Allen L.; Zucchi, Roberto A. (Zootaxa, 2016)
The previously poorly known species Anastrepha luederwaldti Lima, 1934 is redescribed based on a reexamination of the syntypes from São Paulo and additional specimens from Santa Catarina and Rio Grande do Sul, Brazil. A lectotype is designated.